Reading English as a foreign language: The interplay of abilities and strategies - Al-Qahtani, Abdulkhaleq Abdulhadi (Indonesian Journal of Applied Linguistics, 2021)
This paper investigates the preferred order of reading strategies at three ability levels by L1 Arabic learners of English in an EFL setting. Then it explores whether there was a relationship between ability level and strategy use. Ninety-two EFL college students enrolled in a reading comprehension class participated in this study. They took a TOEFL reading section to determine their reading abilities/levels, and then they completed a biographical and the Survey of Reading Strategies (SORS) questionnaires. Then, statistical analyses were conducted. The results showed that each ability level reported strategy use differently in terms of order and intensity. There was also a statistical significance in strategy use between the high ability and the low ability levels. The low ability level participants reported higher use of the global reading strategies than the high ability group. However, no statistical significance of association was found between reading ability and strategy use